Mitigating primary care provider burnout with interdisciplinary dyads and shared care delivery. Issue 3 (5th December 2021) - Norful, Allison A.; He, Yun; Rosenfeld, Adam; Abraham, Cilgy M.; Chang, Bernard
Abstract: Rationale, Aims and Objectives: Increased incidence of chronic illnesses coupled with physician shortages have yielded strain on primary care provider (PCP) to meet care demands. Interdisciplinary providers have increasingly been embedded into primary care teams to alleviate some workload demand. Little evidence exists about the impact of interdisciplinary PCP care delivery models on provider strain in primary care. To determine the impact of interdisciplinary PCP care delivery on burnout, job satisfaction and intention to leave current position. Methods: We conducted a cross‐sectional mail survey using Dillman methodology of primary care practices (e.g., internal medicine) across New York State. A random sample of interdisciplinary PCPs (physicians, nurse practitioners, and physician assistants) ( n = 333) responded. The Provider Comanagement Index ( α = 0.85) was used to measure how well interdisciplinary dyads comanagement care delivery attributes (effective communication; mutual respect and trust; shared philosophy of care). Provider outcomes were measured with validated Agency for Healthcare Research and Quality and Health Resources and Services Administration items for burnout, job satisfaction and intention to leave position. Descriptive statistics, logistic regression models, crude and adjusted odds ratios were calculated, controlling for participant and practice characteristics. Results: Almost 30% of participants reported burnout with three times the odds of intending to leave their current position within 1 year. With each unit increase in effective comanagement between interdisciplinary dyads there was 15% less burnout and 10% less odds of intention to leave position. Conclusion: Incorporating interdisciplinary specialties in primary care appears promising to alleviate some adverse provider outcomes. Organizations contemplating delivery models to promote well‐being and retention may consider comanagement. Cost effectiveness research is needed to determine financial sustainability of interdisciplinary care delivery.